Photoconductivity in pulsed PECVD hydrogenated amorphous silicon thin films - Tong, Goh Boon; Han, Shi Chee; Richard, Ritikos; Rasat, Muhamat Muhamad; Abdul, Rahman Saadah (2006)
Hydrogenated Amorphous Silicon (a-Si:H) thin films were deposited using a pulsed plasma enhanced chemical vapor deposition (PECVD) system developed in our laboratory. The pulsed discharge has been shown to allow deposition at higher power without deteriorating the film properties. In this work, we report our work on the photoconductivity studies done on this pulsed PECVD a-Si:H films. Photoconductivity in these films showed strong dependence on the discharge power and silane flow-rate. Optical parameters obtained from the optical transmission spectra in the ultra-violet visible region of these films were analyzed together with the photoconductivity results. This analysis was used to explain the effects of discharge power on the photoconductivity of the pulsed PECVD a-SiH thin film.